2014
DOI: 10.17221/61/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Relative resistance to Rice yellow mottle virus in rice

Abstract: Salaudeen M.T. (2014): Relative resistance to Rice yellow mottle virus in rice. Plant Protect. Sci., 50: 1-7.We identified sources of Rice yellow mottle virus (RYMV) resistance in rice cultivars. Eight cultivars together with susceptible and resistant controls were evaluated under screenhouse conditions as inoculated and uninoculated treatment in completely randomised design with three replications. Seedlings were inoculated with the virus by sap transmission at two weeks after sowing. Disease incidence and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Within the four locations visited, RYMVD leaf symptoms severity was mild (2.0) in three of the varieties namely: UT-Rice, Yarkundu and Jemila. Variety Wita (3.3) and Faro 44 (3.9) are close to very severe symptoms, this was like the findings of [21], who found that Faro 44 is vulnerable to virus. The rest of the varieties are severe with an overall mean severity of (2.8) ( Table 4).…”
Section: Discussionsupporting
confidence: 80%
“…Within the four locations visited, RYMVD leaf symptoms severity was mild (2.0) in three of the varieties namely: UT-Rice, Yarkundu and Jemila. Variety Wita (3.3) and Faro 44 (3.9) are close to very severe symptoms, this was like the findings of [21], who found that Faro 44 is vulnerable to virus. The rest of the varieties are severe with an overall mean severity of (2.8) ( Table 4).…”
Section: Discussionsupporting
confidence: 80%
“…, where: S i = disease severity at the ith observation and t i = time (days) at the ith observation [37].…”
Section: Inoculation and Disease Assessmentmentioning
confidence: 99%
“…Several management strategies have been recommended to control the disease but the use of resistant cultivars is the most cost-effective, environment-friendly, and sustainable ( Salaudeen 2014 ). Cultural practices and prophylactic methods are more effective if combined with the use of resistant varieties ( Kouassi et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most rice accessions are susceptible to RYMV ( Sereme et al., 2016 ), including O. glaberrima species in which most sources of resistance to RYMV have been found earlier ( Traore et al., 2015 ). Partially and highly resistant varieties have been identified, but currently the disease is not controlled adequately, and its incidence continues to increase in Africa ( Kouassi et al., 2005 ; Salaudeen 2014 ). In Nigeria, an increase in the incidence of the disease was observed in addition to increase in severity from 30 to 90 % after one year period ( Odedara et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%